New elements for a research agenda on brazilian cities: the growth of real estate wealth and the widening of socio-spatial inequalities (Brazilian Geographical Journal, 2016)
This article presents and analyzes a set of data and information regarding crucial processes for the understanding of transformations of which Brazilian cities have and are undergoing over course of the last ten years. It attempts to bring to light and problematize data and information which enable for a greater understanding of changes which are operated from multiple geographical scales over production process of the urban space. Some analytical clippings shall be utilized. Firstly, there is the introduction of a set of empirical data which aids in the reflection of the recent real estate appreciation wave which took place, albeit in a different manner, over all cities of the urban Brazilian network, ever since the persistent increase in real estate values. The information utilized, though still not quite broadly explored in Brazilian literature, refers to the value of real estate property declared by families to the Brazilian Federal Revenue, the national tax collection authority. Essentially, this is a sample which indicates, on a national scale, the real estate re-appreciation processes in a clear fashion. Secondly, the discussion focuses on the city itself; more particularly on specific geographical sectors which, from socio-economical information provenient from heads of family households, seeks to ascertain alterations in the intra-urban location standards, thus substantiating non-trivial processes of relocation, especially those of families of a higher income. Lastly, this text attempts to articulate the two previously explored dimensions by seeking more consistent hypotheses for a work agenda.